Disintegrating Particles, Non-Local Causation and Category Mistakes: What do Conservation Laws Have to Do with Dualism? - Rehman, Rashad (Conatus - Journal of Philosophy, 2018)
The single most influential and widely accepted objection against any form of dualism, the belief that human beings are both body and soul, is the objection that dualism violates conservation laws in physics. The conservation laws objection against dualism posits that body and soul interaction is at best mysterious, and at worst impossible. While this objection has been both influential from the time of its initial formulation until present, this paper occupies itself with arguing that this objection is a fleeting one, and has successful answers from both scientific and philosophical perspectives. It is to this end that I provide three groups of responses to the conservation laws objection. First, I outline responses which take the ‘laws of nature’ as the proper entry point into the discussion. Secondly, I provide an analysis of those who argue that contemporary quantum physical data requires that the objection itself involves scientifically unjustified premises. Finally, I layout a philosophically oriented answer which argues that the objection is linguistically problematic since its demands on the dualist are categorically fallacious. From these groups of answers, I conclude that while the conservation laws objection has been arguably the most widely accepted objection against dualism, the objection is without philosophical justification.